A Taoist Interpretation: Qiemo (Stage Props) Produced Peking Opera Space - Daiyu, Daiyu; Amirul, Azrul Azizi (Harmonia: Journal of Arts Research and Education, 2025)
This research aims to explore the Taoist philosophical roots of the concept of “the unity of heaven and man” in the stage space of Peking opera, as created by Qiemo (stage props). It employs a case study approach, applies Lefebvre’s triadic spatial theory, and includes fieldwork at the Baoding Chinese Ancient Theater Museum. The findings reveal that the space formed by Qiemo reflects the dialectical relationship between heaven and humans. Specifically, the meaning of Qiemo is not fixed but is defined by the actor, symbolizing the human activation of the universe’s inherent meaning. Inspired by the natural order in Qiemo, actors strive for personal fulfillment, ultimately seeking to achieve “the unity of heaven and human“statue.